Factors Associated with the Intake of Ultra-Processed Cariogenic Foods by Preschoolers During the COVID-19 Pandemic - Aline Fabris de Araujo Crema; Bruna Letícia Vessoni Menoncin; Sandra Patricia Crispim; Fabian Calixto Fraiz (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the characteristics and factors associated with the intake of ultra-processed cariogenic foods (UFC) by preschoolers during the COVID-19 pandemic. Material and Methods: This is a cross-sectional study involving parents of 672 children from two to five years old enrolled at public schools in Curitiba, Brazil. Parents answered a questionnaire about socioeconomic and demographic data, their behavior regarding the dietary education of their children (Parent Mealtime Action Scale - translated and validated for use in Brazil), and children's food intake (qualitative food frequency questionnaire - list of foods based on a report from the Pan American Health Organization). The data were analyzed using Poisson regression analysis (α=0.05). Results: About 43% of parents/guardians reported changes in their children's diet during the pandemic, being that diet got worse and better in 19% and 24% of the cases, respectively. The ultra-processed cariogenic foods with the highest daily intake frequencies were sweetened juices/sweetened drinks (0.52), followed by cookies (0.37), and candies (0.35). Parents with a lower level of education reported a daily frequency of UCF intake 1.36 times higher (PR=1.359; CI 95%: 1.106-1.669) in their children compared to those with a higher level of education. On the other hand, parents'/guardians' report of higher intake and greater offer of fruits and vegetables to children was associated with low UCF intake (PR=0.716; CI 95%: 0.592-0.866). Conclusion: The lower level of formal education of parents/guardians and lower availability of fruits and vegetables were related to higher consumption of ultra-processed cariogenic foods by children.